Knapsack sprayers: effort required for pumping lever operation - Lambrecht,Edson (2019)
ABSTRACT: Various equipment, mainly manual knapsack sprayers, are used to apply agrochemicals by smallholder farmers. They are highlighted by their versatility of use and mainly by their low cost for farmers. Few operator-related studies were reported in the literature regarding the effort required to operate the knapsack sprayer lever. Knapsack sprayers were evaluated regarding the effort required to move their hand levers, reach and maintain the 300 kPa pressure, and return to the initial position. The objective of this study was to evaluate the operator’s effort to operate the hand lever using the “Super magro” biofertilizer as fluid. It was concluded that all knapsack sprayers are within the Consolidation of Labor Laws (CLT) standards regarding the effort required to operate the hand lever. However, restrictions have been reported in some manual knapsack sprayers regarding international standards.